The effects of nutrients and hydrology on shallow lake plankton at Attenborough Nature Reserve, Nottinghamshire - Cross, Iain David (2009)
Eutrophication results in the loss of conservation and amenity value from shallow lakes. Efforts have been made to restore shallow lakes by reducing the external nutrient loading. Removing nutrient-rich inflows can reduce nutrient loading but may alter lake hydrology. This thesis is primarily aimed at investigating the effects of a nutrient-rich river on water chemistry and plankton by comparing six shallow (<3.5 m) lakes that are connected to and isolated from the River Erewash, in the Attenborough Nature Reserve, Nottinghamshire, U.K.